Complicações neurológicas determinadas pela anestesia subaracnóidea - Ganem, Eliana Marisa [UNESP]; Machado Castiglia, Yara Marcondes [UNESP]; Galvão Vianna, Pedro Thadeu [UNESP] (My University, 2002)
Background and Objectives - Although rare spinal anesthesia-induced neurological complications may determine serious sequelae. This study aimed at presenting these complications in order to elucidate triggering factors and help in the diagnosis of such injuries. Contents - The following complications are presented: needle and catheter-induced nerve injury, post dural puncture headache, anterior spinal artery syndrome, spinal hematoma, septic meningitis, aseptic meningitis, adhesive arachnoiditis, cauda equina syndrome, and transient neurological symptoms. Conclusions - The understanding of triggering factors of spinal anesthesia-induced neurological complications may prevent injuries and help early diagnosis and treatment, therefore changing patients prognosis.
Spinal anesthesia-induced neurological complications
Keywords: Anesthetic Techniques, Regional: spinal block; Complications: neurological